2021
DOI: 10.1039/d0fo02684k
|View full text |Cite
|
Sign up to set email alerts
|

Aloin protects mice from diet-induced non-alcoholic steatohepatitis via activation of Nrf2/HO-1 signaling

Abstract: Aloin, a naturally occurring anthraquinone glycoside derived from the Aloe species, has antioxidant and anti-inflammatory activities, but its role in non-alcoholic steatohepatitis (NASH) remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…However, searching for effective treatment drugs for IDD is still a huge challenge. Aloin, extracted from aloe plants, has been shown to have anti-inflammatory, antioxidant, and bone protective activities, but its effects on IDD have not been confirmed [ 37 , 38 , 40 ]. In our study, we demonstrated that aloin treatment can reverse TNF- α -induced extracellular matrix metabolism disorder, apoptosis, oxidative stress, and the production of proinflammatory factors in NPCs through the TAK1/NF- κ B/NLRP3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, searching for effective treatment drugs for IDD is still a huge challenge. Aloin, extracted from aloe plants, has been shown to have anti-inflammatory, antioxidant, and bone protective activities, but its effects on IDD have not been confirmed [ 37 , 38 , 40 ]. In our study, we demonstrated that aloin treatment can reverse TNF- α -induced extracellular matrix metabolism disorder, apoptosis, oxidative stress, and the production of proinflammatory factors in NPCs through the TAK1/NF- κ B/NLRP3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Aloin, also known as barbaloin, is a natural aloe- derived anthraquinone compound that can ameliorate oxidative stress, anti-apoptosis and anti-inflammation on liver diseases ( 114 , 115 ). A recent study also revealed that aloin can enhance antioxidant, anti-inflammatory and anti-apoptotic activity by activating Nrf2/HO-1 signaling in Nrf2 KO (Nrf2−/−) C57BL/6 mice model fed CDAAH diet models ( 116 ). Moreover, aloin could reduce oxidative stress, liver inflammation in rats fed HFHFD ( 18 ).…”
Section: Herbs and Active Tcm Ingredientsmentioning
confidence: 99%
“…Moreover, a research suggested that Aloe vera extract may hold promise in the treatment of ulcerative colitis by enhancing colon mucus secretion . In addition, aloin also protected mice from diet-induced nonalcoholic steatohepatitis . Another important property of aloin is its anticancer effect, which has been demonstrated in various animal models of cancer, such as colorectal, liver, and gastric cancers. However, as far as we know, the use of aloin has not been reported in liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%